Proton and Metal Dication Affinities of Tetracyclic Imidazo[4,5-b]Pyridine-Based Molecules: Insights from Mass Spectrometry and DFT Analysis - Lucija Vrban; Ingrid Ana Martinac; Marijana Hranjec; Marijana Pocrnić; Nives Galić; Renata Kobetić; Robert Vianello (Molecules)
The imidazo[4,5-b]pyridine scaffold, a versatile heterocyclic system, is renowned for its biological and chemical significance, yet its coordination chemistry with biologically relevant metal dications remains underexplored. This study investigates the proton and metal dication affinities of twelve tetracyclic organic molecules based on the imidazo[4,5-b]pyridine core, focusing on their interactions with Ca(II), Mg(II), Zn(II), and Cu(II). Employing a dual approach of electrospray ionization mass spectrometry (ESI-MS) and density functional theory (DFT) calculations, we characterized the formation, stability, and structural features of metal–ligand complexes. ESI-MS revealed distinct binding behaviors, with Cu(II) and Zn(II) forming stable mono- and dinuclear complexes, often accompanied by reduction processes (e.g., Cu(II) to Cu(I)), while Ca(II) and Mg(II) exhibited lower affinities. DFT analysis elucidated the electronic structures and thermodynamic stabilities, highlighting the imidazole nitrogen as the primary binding site and the influence of regioisomeric variations on affinity. Substituent effects were found to modulate binding strength, with electron-donating groups enhancing basicity and metal coordination. These findings provide a comprehensive understanding of the coordination chemistry of imidazo[4,5-b]pyridine derivatives, offering insights into their potential applications in metalloenzyme modulation, metal-ion sensing, and therapeutic chelation.